OPTIMIZATION OF THE CNC MILLING PROCESS VIA MODIFYING SOME PARAMETERS OF THE CUTTING MODE WHEN PROCESSING QUERCUS ROBUR L. - Doichinov, Alexander (Innovation in Woodworking Industry and Engineering design, 2025)
ak wood (Quercus robur L.) parts processed on a CNC woodworking milling-drilling center. The present study aims to determine the combined effect of key cutting parameters such as spindle speed (n), feed rate (V f ) and depth of cut (h). The evaluation of the milled surfaces was conducted based on the roughness parameter Rz , with measurements taken using an electronic profilometer model Surftest SJ-210 (Mitutoyo, Japan). As a result of the conducted experiments, graphical dependencies were derived, illustrating the degree of influence of the studied factors on the surface roughness of the machined parts.